(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Background. The aim of the study was to estimate the population of children that underwent ultrasonography in the inpatient and outpatient conditions of a hospital for children for the evaluation of reserves of the improvement of the existing ultrasonography service. Materials and Methods. The method of expert evaluation was used to perform the analysis of medical documentation of 2606 children aged 0-18 years old that underwent ultrasonography. The authors studied the demographic data, the number of previous ultrasonography, the speciality of the doctor that directed for the investigation, presence of chronic diseases in a child, and the type of the performed ultrasonography. Results. The authors established the age differences: the highest rate of inpatient population was among neonates and outpatient population – among 1-3 year-old children. In the majority of cases, children were directed for ultrasonography by inpatient specialists. In outpatient conditions, primarily, cardiologists and cardiosurgeons directed children for ultrasonography. Nearly in all the age groups, the mean number of repeated investigations was lower in outpatient conditions. Among neonates, there were no repeated investigations. In the structure of morbidity in children in inpatient conditions, the most widespread diseases were diseases of the nervous system, skin and subcutaneous tissue, musculoskeletal and urogenital systems, and perinatal conditions. In outpatient conditions, infectious diseases and neoplasms were the most widespread. It was established that there were no significant differences in the distribution of inpatient and outpatient children by the types of ultrasonography. The leading places are occupied by the investigation of organs of the abdominal cavity, kidneys and retroperitoneum, and system of blood circulation. Conclusion. It is proposed to use the obtained results for the study of the peculiarities of the population of children that underwent ultrasonography in the inpatient and outpatient conditions. The obtained data can be used for planning of the required volume of different diagnostic services at different levels.